ANALISIS GAYA KEPEMIMPINAN, LINGKUNGAN KERJA, MOTIVASI KERJA, KINERJA KARYAWAN PADA SYARIAH RADHO HOTEL MALANG - M. Aryo Tri Satya Graha; Hadi Sunaryo; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG)
ABSTRACT This study aims to describe the variables of leadership style, work environment, work motivation and employee performance in Radho Malang Syariah Hotels. From the results of this study, population data is 50 people and the sample is the same as the population, because it uses a census technique based on a population of less than 100 people. This research is located in Syariah Radho Hotel Malang. Data collection uses primary data using the questionnaire method to respondents. Data analysis method uses descriptive statistics. The test equipment in this study used validity and rebility tests. Obtained leadership style variables reflected by indicators of intelligence (Intelligence). The variables of the work environment are reflected by the indicators of relations between employees. Variable work motivation is reflected by indicators of self-actualization needs. employee performance variables are reflected by the quantity indicator. Keywords: Leadership Style, Work Environment, Work Motivation, Employee Performance, Descriptive Statistics